The Haar Wavelet Transform in IoT Digital Audio Signal Processing - Escola, João Paulo Lemos; de Souza, Uender Barbosa; Guido, Rodrigo Capobianco [UNESP]; Silva, Ivan Nunes da (Springer Nature, 2022)
Digital signal processing allows a wide range of digital applications, including audio processing. Discrete wavelet transform (DWT) is one of the most efficient ways of time–frequency analysis of an audio signal. The Internet of Things (IoT) is a technology that has been growing in commercial automation applications with the availability of low-cost modules and microcontrollers. IoT projects that use DWT for digital audio processing can solve many problems involving audio signals. In this paper, a performance comparison of an algorithm implementing DWT on three commercially available IoT devices is presented. The results show that it is possible to process signals in the 256 Hz to 6.5 KHz range, opening possibilities for future work integrating the technologies described.
Keywords: Digital Signal Processing; Internet of Things; Performance analysis; Wavelets